Evaluasi Kejadian Missfile Rekam Medis menggunakan Metode Focus PDCA di RSUP Sanglah - Fahirah Tamara Salim; Atma Deharja; Ervina Rachmawati (Politeknik Negeri Jember, 2020)
There were 482 medical file missfile incidents in 2019, with the highest number occurring in June 2019 with 61 medical record misfile, this could cause officers to experience difficulties in searching for medical record files and increasing the work of officers to more busy because they have to do a search on other number shelves that allow it to be misplaced, so the service process tends longer. This research aims to evaluate the event of medical record misfile using the FOCUS PDCA method at Sanglah Hospital Denpasar. Data collection techniques used in this research were interviews and observation. The data analysis stage in this research includes the identification of stage of find, organized, clarify, understand, select, plan, do, check, and action. The solution chosen to solve the problem is by designing the media information about the range of medical record storage on each shelf, carrying out the process of attached numbering information media to each storage shelf, and conducting information dissemination related to the attached media. The results of this evaluation are storing medical record files that are arranged according to the number on the shelf and re-monitoring at the end of every month all medical records in the place.